Serially measured circulating microRNAs and adverse clinical outcomes in patients with acute heart failure. (25th September 2017) - van Boven, Nick; Kardys, Isabella; van Vark, Laura C.; Akkerhuis, K. Martijn; de Ronde, Maurice W.J.; Khan, Mohsin A.F.; Merkus, Daphne; Liu, Zhen; Voors, Adriaan A.; Asselbergs, Folkert W.; van den Bos, Ewout‐Jan; Boersma, Eric; et al.
Abstract : Aims: Previous studies have identified candidate circulating microRNAs (circmiRs) as biomarkers for heart failure (HF) using relatively insensitive arrays, validated in small cohorts. The present study used RNA sequencing to identify novel candidate circmiRs and compared these with previously identified circmiRs in a large, prospective cohort of patients with acute HF (AHF). Methods and results: RNA sequencing of plasma from instrumented pigs was used to identify circmiRs produced by myocardium. Production of known myomiRs and microRNA (miR)‐1306‐5p was identified. The prognostic values of this and 11 other circmiRs were tested in a prospective cohort of 496 AHF patients, from whom blood samples were collected at up to seven time‐points during the study's 1‐year follow‐up. The primary endpoint was the composite of all‐cause mortality and HF rehospitalization. In the prospective AHF cohort, 188 patients reached the primary endpoint, and higher values of repeatedly measured miR‐1306‐5p were positively associated with risk for reaching the primary endpoint at the same time‐point [hazard ratio (HR) 4.69, 95% confidence interval (CI) 2.18–10.06], independent of clinical characteristics and NT‐proBNP. Baseline miR‐1306‐5p did not improve model discrimination/reclassification significantly compared with NT‐proBNP. For miR‐320a, miR‐378a‐3p, miR‐423‐5p and miR‐1254, associations with the primary endpoint were present after adjustment for age and sex (HR 1.38, 95% CI 1.12–1.70; HR 1.35, 95% CI 1.04–1.74; HR 1.45, 95% CI 1.10–1.92; HR 1.22, 95% CI 1.00–1.50, respectively). Rates of detection of myomiRs miR‐208a‐3p and miR‐499a‐5p were very low. Conclusions: Repeatedly measured miR‐1306‐5p was positively associated with adverse clinical outcome in AHF, even after multivariable adjustment including NT‐proBNP. However, baseline miR‐1306‐5p did not add significant discriminatory value to NT‐proBNP. Low‐abundance, heart‐enriched myomiRs are often undetectable, which mandates the development of more sensitive assays.